Seasonal Variation: A Non-negligible Factor Associated With Blood Pressure in Patients Undergoing Hemodialysis - Wu, Zhibin; Lan, Shan; Chen, Chengqiang; Zhang, Xiuan; Zhang, Yazhen; Chen, Shanying (Frontiers in Cardiovascular Medicine, 2022)
Abstract Objective: To investigate seasonal variation of blood pressure (BP) in patients undergoing hemodialysis (HD). Methods: In this retrospective study, we exported all BP measurements from the information system to investigate seasonal variation in BP. We also investigated seasonal variation of BP in different gender, different age groups, diabetic nephropathy (DN) and non-DN patients with HD. Multiple linear regression models were used to explore the associations between BP and climatic parameters. Results: During 2019, a total of 367 patients had received HD therapy in Longwen HD unit. We included nearly 40,000 pre-dialysis BP measurements. The result of our study demonstrated a clear seasonal variation in pre-dialysis BP in general HD patients, in male & female, and in DN & non-DN patients. December peaked in values of pre-dialysis systolic BP (SBP) and diastolic BP (DBP). The nadir values of pre-dialysis SBP and DBP were observed in June and July, respectively. Difference between peak and nadir values of BP is 3.81 /2.20 mmHg in patients undergoing HD. Maximal seasonal variation of BP is 9.03/5.08 mmHg in patients with DN. A significant association of SBP and DBP with climatic parameters was found in the present study. The pre-dialysis BP was inversely correlated with outdoor temperature, daytime length and relative humidity. Conclusion A clear seasonal variation of BP is observed in patients with HD. Pre-dialysis SBP and DBP are inversely associated with outdoor temperature, daytime length and relative humidity. The magnitude of seasonal variation in BP increases in DN patients.